2009
DOI: 10.1097/tp.0b013e3181a484d7
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcomes of Thymoglobulin and Basiliximab Induction in Kidney Transplantation: Application of Statistical Approaches to Reduce Bias in Observational Comparisons

Abstract: Background-Retrospective comparison of treatment-related kidney transplant outcomes may be facilitated by multivariable statistical adjustments and case-matching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 25 publications
0
51
0
Order By: Relevance
“…It was suggested that more potent induction therapy with thymoglobulin can decrease the incidence of acute rejection and may prolong graft survival in high risk patients. [24][25][26] Therefore, induction with a T-cell depleting antibody should be considered for HLA-6-antigen mismatched deceased-donor kidney transplants. oe This study provides the fi rst singlecenter data examining the effect of HLA match on long-term graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that more potent induction therapy with thymoglobulin can decrease the incidence of acute rejection and may prolong graft survival in high risk patients. [24][25][26] Therefore, induction with a T-cell depleting antibody should be considered for HLA-6-antigen mismatched deceased-donor kidney transplants. oe This study provides the fi rst singlecenter data examining the effect of HLA match on long-term graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…2,22 With the development of ATG induction and maintenance immunosuppression with mycophenolate mofetil, tacrolimus, and steroids, rejection rates have decreased. 9,[11][12][13][14] Transplant kidney biopsy, the criterion standard for diagnosing rejection, is usually performed after the transplant in patients with DGF. The timing of these posttransplant biopsies in the setting of DGF remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Antithymocyte globulin use is associated with significant reduction in the incidence of acute rejection, graft loss, and patient death when used with tacrolimus, and mycophenolate mofetil, and with and without steroids. 14 Renal allograft biopsy remains the criterion standard for diagnosing rejection. In the setting of DGF, it has been recommended that biopsies be performed at 1-week intervals, starting 7 days after surgery.…”
mentioning
confidence: 99%
“…Alemtuzumab and emergence of some autoimmune diseases. This effect has been attributed to memory T-cell 56 . ATG is the agent studied extensively due to its significant beneficial impact on the recipient and graft, to standardized its dose and establish a minimum dose benefit ratio in order to avoid untoward effects which could result due to higher dosages.…”
Section: And54mentioning
confidence: 99%